Distingsi dan Tujuan Model Bisnis - Mimbha Nur Indhasari; Jeni Susyanti (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
A business model is a basic framework that explains how organizations create, deliver, and capture value. This paper discusses the distingsi or differences between various business models and identifies the main objectives of each model. Through a review of classical and contemporary models, this paper highlights the importance of strategy in choosing the right business model to achieve sustainable competitive advantage. This study uses a descriptive-qualitative approach with literature study and case study as the main methods